A transmedia project about the armed conflict in Colombian Coffee Axis - López-Chica, Paula; Soto, Juliana; Montoya-Ballesteros, Daniel; Bustos-Villalba, Juana V.; Pineda, Jefferson; Arango-Giraldo, Pablo R. (Arte, Individuo y Sociedad, 2023)
This article presents the results of a transmedia investigation project that gathered a variety of voices to recreate some of the individual and collective experiences from the Colombian armed conflict in the region known as the Colombian Coffee axis. In addition to the creation of a series of works, integrated by a transmedia narrative, the project shows the functionality of transmedia projects when it comes to the double task of contributing to the reconstruction of historic memory in the conflict and reaching diverse audiences in different formats. In addition, the project reveals the existence of a scattered yet persistent consciousness about the horrors lived in the armed conflict in the Coffee axis, a region that in the official versions and social narrative appears as a region of peace and prosperity associated with the cultivation of coffee. To achieve this, the project publicly called for the participation of different people, so they could tell their story in some cases, and show the results of their investigative and creative works in others. In this way, the project articulated voices and subjectivities that are usually expressed through separate channels.